The Cossack Uprisings of the Late 16th and Early 17th Centuries in Ukrainian History Textbooks: An Attempt to Assess the Concept - Kovalets, Taras (My University, 2023)
Kovalets T. The Cossack Uprisings of the Late 16th and Early 17th Centuries in Ukrainian History Textbooks: An Attempt to Assess the Concept // Dialog intercultural polono-moldovenesc: Culegere de studii. Materialele Congresului ştiinţific internaţional Moldo-Polono-Român: Educaţie-Politici-Societate. Chişinău-Cracovia 13-15 martie 2023 : [în vol.] / col. red.: Valentin Constantinov (Moldova), Norbert Pikula (Cracovia-Polonia) [et al.]. P. 51-53.